2017
DOI: 10.1098/rspb.2017.0350
|View full text |Cite
|
Sign up to set email alerts
|

Food web persistence in fragmented landscapes

Abstract: Habitat destruction, characterized by patch loss and fragmentation, is a key driver of biodiversity loss. There has been some progress in the theory of spatial food webs; however, to date, practically nothing is known about how patch configurational fragmentation influences multi-trophic food web dynamics. We develop a spatially extended patch-dynamic model for different food webs by linking patch connectivity with trophic-dependent dispersal (i.e. higher trophic levels displaying longer-range dispersal). Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 67 publications
1
40
0
Order By: Relevance
“…Thus, a larger branch contains more patches (illustrated in Figure 1; Muneepeerakul, Weitz, Levin, Rinaldo, & Rodriguez-Iturbe, 2007). The population of a given branch, and the system as a whole, can be regarded as proportional to the number of colonised patches within it (Liao, Bearup, & Blasius, 2017a;Liao, Bearup, & Blasius, 2017b;Liao et al, 2017). This framework allows us to model both within-branch colonisation-extinction processes and the effects of dispersal between branches.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thus, a larger branch contains more patches (illustrated in Figure 1; Muneepeerakul, Weitz, Levin, Rinaldo, & Rodriguez-Iturbe, 2007). The population of a given branch, and the system as a whole, can be regarded as proportional to the number of colonised patches within it (Liao, Bearup, & Blasius, 2017a;Liao, Bearup, & Blasius, 2017b;Liao et al, 2017). This framework allows us to model both within-branch colonisation-extinction processes and the effects of dispersal between branches.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Given that top-down regulation can stabilise food webs [24,57], the loss of top predators might entail unpredictable consequences for adjacent trophic levels, destabilise food webs, reduce species diversity and trophic complexity and ultimately compromise ecosystem functioning [23,24]. In addition to the trophic position of a species, the trophic structure of the food web has also been shown to be an important aspect (see [11]). Our results suggest that bottom-up energy limitation caused by dispersal mortality due to habitat isolation can be a critical factor driving species loss and the reduction of trophic complexity.…”
Section: The Biggest Losersmentioning
confidence: 99%
“…A general observation and prediction is that large-bodied predators at high trophic levels which depend on sufficient food supplied by lower trophic levels are most sensitive to fragmentation, and thus, might respond more strongly than species at lower trophic levels [4,5]. However, most conclusions regarding the effect of fragmentation are based on single species or competitively interacting species (see references within [6][7][8], but see for example [9][10][11] for food chains and simple food web motifs). There is thus limited understanding how species embedded in complex food webs with multiple trophic levels respond to habitat fragmentation [4,[12][13][14][15], even though these networks are a central organising theme in nature [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Habitat loss refers to a 65 decrease in the amount of suitable habitat whereas fragmentation per se implies a decrease in the 66 spatial autocorrelation of suitable habitat (Jackson and Fahrig, 2013;Fahrig, 2017). It is important to 67 study both effects independently, as each has a distinct effect on species performance within multi-68 trophic food webs (Liao, Bearup and Blasius, 2017). Habitat loss generally has negative effects on 69 species survival, whereas fragmentation might promote species coexistence within a trophic level by 70 lowering competition and between trophic levels by providing refuges Fahrig, 2013, 71 2015;Fahrig, 2017;Liao, Bearup and Blasius, 2017;Fletcher Jr et al, 2018).…”
Section: Introduction 25mentioning
confidence: 99%
“…It is important to 67 study both effects independently, as each has a distinct effect on species performance within multi-68 trophic food webs (Liao, Bearup and Blasius, 2017). Habitat loss generally has negative effects on 69 species survival, whereas fragmentation might promote species coexistence within a trophic level by 70 lowering competition and between trophic levels by providing refuges Fahrig, 2013, 71 2015;Fahrig, 2017;Liao, Bearup and Blasius, 2017;Fletcher Jr et al, 2018). So far, theoretical studies 72 have demonstrated that large individuals can be selected with increasing levels of isolation and 73 habitat fragmentation due to their high gap-crossing ability (Etienne and Olff, 2004;Hillaert, 74 Hovestadt, et al, 2018).…”
Section: Introduction 25mentioning
confidence: 99%